2010
DOI: 10.1101/gr.106542.110
|View full text |Cite
|
Sign up to set email alerts
|

Changes in H2A.Z occupancy and DNA methylation during B-cell lymphomagenesis

Abstract: The histone variant H2A.Z has been implicated in the regulation of gene expression, and in plants antagonizes DNA methylation. Here, we ask whether a similar relationship exists in mammals, using a mouse B-cell lymphoma model, where chromatin states can be monitored during tumorigenesis. Using native chromatin immunoprecipitation with microarray hybridization (ChIP-chip), we found a progressive depletion of H2A.Z around transcriptional start sites (TSSs) during MYC-induced transformation of pre-B cells and, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
93
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 34 publications
14
93
0
1
Order By: Relevance
“…A greater understanding of the role of macroH2A in cancer progression might provide a diagnostic tool for deciding therapeutic strategies. Work in Arabidopsis has demonstrated the mutual antagonism between DNA methylation and H2A.Z occupancy, with this pattern also being observed in normal mammalian cells and during tumorigenesis (Zilberman et al, 2008;Conerly et al, 2010). Although the mechanism behind this interdependence is unclear, loss of H2A.Z at tumor suppressor genes could lead to DNA methylation and heritable repression, consistent with the observation that deposition of H2A.Z is required for the full reactivation of silent genes following 5-AzaC treatment (Yang et al, 2012).…”
Section: Histone Variants In Human Diseasesupporting
confidence: 59%
“…A greater understanding of the role of macroH2A in cancer progression might provide a diagnostic tool for deciding therapeutic strategies. Work in Arabidopsis has demonstrated the mutual antagonism between DNA methylation and H2A.Z occupancy, with this pattern also being observed in normal mammalian cells and during tumorigenesis (Zilberman et al, 2008;Conerly et al, 2010). Although the mechanism behind this interdependence is unclear, loss of H2A.Z at tumor suppressor genes could lead to DNA methylation and heritable repression, consistent with the observation that deposition of H2A.Z is required for the full reactivation of silent genes following 5-AzaC treatment (Yang et al, 2012).…”
Section: Histone Variants In Human Diseasesupporting
confidence: 59%
“…One of these examined genome-wide DNA methylation in the same genetically driven Eµ-Myc mouse model of Burkitt lymphoma used in our current study. 31 Robust promoter CpG island DNA hypermethylation of individual genes was not described, but rather only a trend toward increasing promoter CpG island DNA hypermethylation could be discerned when data for all genes were analyzed in aggregate. A separate study in Eµ-Myc mice demonstrated a modest increase in DNA methylation by transgenic expression of DNMT3B7, a truncated isoform of DNA methyltransferase 3B that has been found in human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The unstable dimer is collapsible, highly acetylated and enables chromatin expansion and nucleosome ejection at areas of unmethylated DNA targeted for active expression. 89 Unstable histone variants such as H2A.Z most often coincide with transcription start sites 90,91 and are highly concentrated in euchromatin marked with acetylated H3K9, H3K18, H3K27 and H4 tails circumscribing open 5' promoter regions of genes. 92,93 While methylation of histone tails is primarily associated with silencing, triple methylation at H2AR at serine residues within the H3 tail by enzymes such as PRMT5 are also associated with H2A.Z core exchange, unit collapse, nucleosomal ejection and active gene expression.…”
Section: Nucleosomal Positioningmentioning
confidence: 99%